2020
DOI: 10.1155/2020/9025847
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Endodontic Management of an Immature Molar Using Calcium Hydroxide and Triple Antibiotic Paste: a Two-Year Follow-Up

Abstract: The regenerative endodontic procedure (REP) is considered a viable treatment option for immature teeth with necrotic pulp and periapical radiolucency which can facilitate continued root formation. In this report, an immature necrotic mandibular molar received REP in three appointments wherein chemomechanical debridement was performed with a sequential application of nonsetting calcium hydroxide (in the whole canal) and triple antibiotics paste (in the root’s middle third) dressings in the first and second appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…It confirmed a normal periapical tissue and complete roots formation. A positive response to cold test was obtained after 3 years and this is similar to another study's finding in which the authors reported a positive response to cold in an immature molar tooth with a coronal MTA plug [34].…”
Section: Discussionsupporting
confidence: 89%
“…It confirmed a normal periapical tissue and complete roots formation. A positive response to cold test was obtained after 3 years and this is similar to another study's finding in which the authors reported a positive response to cold in an immature molar tooth with a coronal MTA plug [34].…”
Section: Discussionsupporting
confidence: 89%
“…The search culminated in forty-six studies that fulfilled both the inclusion and exclusion criteria. The review included randomized controlled trials, controlled clinical trials, case reports, in vitro with in vivo studies, in vivo studies, and prospective/retrospective studies comparing the effectiveness of pulp revascularization in immature necrotic permanent teeth [ 3 , 4 , 6 , 16 , 20 , 22 , 26 65 ]. The studies included in this systematic review were 31 human studies [ 3 , 4 , 6 , 16 , 20 , 22 , 26 31 , 35 , 39 , 40 , 44 47 , 50 53 , 55 – 57 , 59 , 60 , 63 65 ] and 15 animal studies [ 32 34 , 36 38 , 41 43 , 48 , 49 , 54 , 58 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review evaluated 46 studies that included a study sample of 1006 subjects (teeth). The human studies included patients of children and young individuals (aged between 7 and 18 years) with a mean age (mean ± SD) 10.1 ± 3.18 years and selected from different dental clinics, hospitals, and dental schools [ 3 , 4 , 6 , 16 , 20 , 22 , 26 31 , 35 , 39 , 40 , 44 47 , 50 53 , 55 – 57 , 59 , 60 , 63 65 ]. On the other hand, most of the samples in animal studies included different species such as ferrets, sheep, dogs, and monkeys [ 32 34 , 36 38 , 41 43 , 48 , 49 , 54 , 58 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If TAP is to be used for ERP, it should be employed at a concentration of 1–5 mg/mL as recommended/prescribed by the “American Association of Endodontists” [ 6 , 8 ]. Furthermore, other materials and systems have been considered for ERP to achieve root canal disinfection, namely, calcium hydroxide as an intracanal medicament [ 8 , 9 ] and the newly devised three-dimensional drug delivery construct, which seems to be a promising potential as a disinfection strategy for RE [ 10 ].…”
Section: Introductionmentioning
confidence: 99%